1998
DOI: 10.1007/s002689900396
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and Inflammatory Bowel Disease: Bias, Epidemiology, Surveillance, and Treatment

Abstract: Individuals with chronic ulcerative colitis are at increased risk of developing colorectal carcinoma, particularly if there is long-standing disease or extensive colitis. It is generally accepted that the risk of colorectal cancer does not begin until 8 to 10 years after the time of diagnosis of ulcerative colitis. Thereafter it increases by approximately 0.5% to 1.0% per year. In patients with Crohn's disease, the risk of malignancy is smaller and less well defined. The most significant predictor of the risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 69 publications
0
20
0
1
Order By: Relevance
“…A meta-analysis looking at the risk of colorectal cancer in patients with UC by decade of disease and defining the risk in pancolitis found a non-significant increase in risk over time [29]. An earlier paper by Solomon and Schnitzler [30]reviewing the same subject in patients with UC concluded that the cancer risk in such patients is increased, particularly if the disease is long-standing or extensive. The risk of cancer begins to increase after the first decade of life by 0.5–1.0% per year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis looking at the risk of colorectal cancer in patients with UC by decade of disease and defining the risk in pancolitis found a non-significant increase in risk over time [29]. An earlier paper by Solomon and Schnitzler [30]reviewing the same subject in patients with UC concluded that the cancer risk in such patients is increased, particularly if the disease is long-standing or extensive. The risk of cancer begins to increase after the first decade of life by 0.5–1.0% per year.…”
Section: Discussionmentioning
confidence: 99%
“…These new modalities will identify those with a high probability of developing colorectal cancer. As gastroenterologists involved in cancer screening in such patients, we have to keep in mind the limitations of colonoscopy in identifying all the early cases [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many chronic inflammatory diseases, such as ulcerative colitis, are associated with a high incidence of cancer (54). In addition, blood vessels surrounding human colorectal cancers overexpress NK-1 (55).…”
Section: Discussionmentioning
confidence: 99%
“…An increased risk for adenocarcinoma in small bowel Crohn’s disease has been suggested [23, 24, 25, 26]. The possibility for the development of cancer in the afflicted segment with inflammatory tissue left in situ with strictureplasty has been discussed, and some authors suggested consideration of frozen sections intraoperatively in cases with suspect morphologic features [27, 28].…”
Section: Discussionmentioning
confidence: 99%